Why Does Piscirickettsia salmonis Break the Immunological Paradigm in Farmed Salmon? Biological Context to Understand the Relative Control of Piscirickettsiosis - Rozas-Serri, Marco (Frontiers in Immunology, 2022)
Piscirickettsiosis (SRS) has been the most important infectious disease in Chilean salmon farming since the 1980s. It was one of the first to be described, and to date, it continues to be the main infectious cause of mortality. How can we better understand the epidemiological situation of SRS? The catch-all answer is that the Chilean salmon farming industry must fight year after year against a multifactorial disease, and apparently only the environment in Chile seems to favor the presence and persistence of Piscirickettsia salmonis. This is a fastidious, facultative intracellular bacterium that replicates in the host's own immune cells and antigen-presenting cells and evades the adaptive cell-mediated immune response, which is why the existing vaccines are not effective in controlling it. Therefore, the Chilean salmon farming industry uses a lot of antibiotics—to control SRS—because otherwise, fish health and welfare would be significantly impaired, and a significantly higher volume of biomass would be lost per year. How can the ever-present risk of negative consequences of antibiotic use in salmon farming be balanced with the productive and economic viability of an animal production industry, as well as with the care of the aquatic environment and public health and with the sustainability of the industry? The answer that is easy, but no less true, is that we must know the enemy and how it interacts with its host. Much knowledge has been generated using this line of inquiry, however it remains insufficient. Considering the state-of-the-art summarized in this review, it can be stated that, from the point of view of fish immunology and vaccinology, we are quite far from reaching an effective and long-term solution for the control of SRS. For this reason, the aim of this critical review is to comprehensively discuss the current knowledge on the interaction between the bacteria and the host to promote the generation of more and better measures for the prevention and control of SRS.